دراسة مقارنة لمستوى بعض عناصر اللياقة البدنية - جبايلي, لياس; بزيو, سليم (جامعة الوادي - University of Eloued, 2022)
هدفت هذه الدراسة إلى محاولة معرفة الفروق بين تلاميذ المرحلة المتوسطة في بعض عناصر اللياقة البدنية (التحمل، القوة، السرعة والرشاقة ، وتبلورت مشكلة الدراسة في التساؤل التالي : هل توجد فروق ذات دلالة احصائية في مستوى بعض عناصر اللياقة البدنية (التحمل، القوة، السرعة، الرشاقة) لدى تلاميذ المرحلة المتوسطة بين تلاميذ منطقة خنشلة ومنطقة بسكرة ؟ هذا واعتمد الباحث في هذه الدراسة على المنهج الوصفي المقارن ،كما اعتمد الباحث على عينة قصدية والمتمثلة في تلاميذ المرحلة المتوسطة (12-14 سنة) من متوسطتين، ثانوية بمنطقة بسكرة (45 تلميذ) و ثانوية بمنطقة خنشلة (45 تلميذ)، وباعتماد على الاختبارات البدنية التي تقيس كل من عناصر اللياقة البدنية (التحمل، القوة، السرعة، الرشاقة)،حيث اعتمد الباحث على الاختبارات البدنية كأداة لجمع البيانات وهي (الجري-المشي لمدة 6 دقائق، الوثب من الثبات، العدو 30 متر، الجري الزجزاجي ،وتوصل الباحث إلى انه لا توجد فروق ذات دلالة إحصائية بين نتائج تلاميذ المرحلة المتوسطة لمنطقة بسكرة ولمنطقة خنشلة في العناصر الأربعة (التحمل، القوة، السرعة، الرشاقة). Abstract: this study was designed to try to understand the differences between middle-level student in certain elements of fitness (endurance, strength, speed and agility), and crystallized the study problem in the following question: is there a statistically significant difference in the medium level some elements of differences in fitness (endurance, strength, speed, agility) among students of the average level between students of the Khenchela and Biskra region? This adopted a researcher in this study on descriptive and comparative, as a deliberately supported researcher and sample of students of the average level (12-14 years) of middle school in the Biskra region (45 students) and of middle school in the Khenchela region (45 students), and the adoption of physical tests that measure the elements of physical condition (endurance , strength, speed, agility), where the researcher based on physical tests as a tool to collect data that is (running for 6 minutes, jumping in support, running speed of 30 meters, running zig-zag), the researcher concluded that there was no fur Statistically significant differences between the results of high school students for the region of Biskra and Khenchela in the four elements (endurance , strength, speed, agility)
مقال
Keywords: اللياقة البدنية ؛ التحمل ؛ القوة؛ السرعة ؛ الرشاقة; fitness; endurance; strength; speed; agility